Análise da aprendizagem dos componentes curriculares - Latim I e II: um estudo de caso do curso de Letras – Português da Universidade Federal do Pará - DIAS, Dhemiff Quaresma (2022)
The Latin learning makes part of the Disciplines of the Letters Curse- with habilitation in teaching Portuguese from the Federal University of Pará, in this context, this work aims to analyze the learning difficulties that students find during the course. The research was conducted through a questionnaire applied individually disponible by an online link which identified the difficulties students got when they studied the component Latin.